Perencanaan Inovasi Smart Mobility Sebagai Pendeteksi Jalan Raya Rusak di Kota Yogyakarta - Nababan, Yohanna Kristia; Mukminah, Sulthanah; Syamsu, Damar Albaribin (Social and Political Science Faculty - Universitas Tidar, 2023)
This research aims to answer the obstacles to implementing smart cities, especially the smart mobility component due to road damage in Yogyakarta City with one of the locations where there are damaged roads or potholes, namely on Jalan Balirejo, Muja Muju, Kec. Umbulharjo, Yogyakarta City. The research method used is a literature study method with a qualitative approach to examine problems using journal articles and books that have relevance to the research so that the results are validated. The results of this research show that road damage is the government's responsibility to maintain and repair it. However, the main obstacle is that the road maintenance survey process to check road conditions is only carried out over a 1-2 year period. This time is quite long for the city of Yogyakarta which carries the smart city concept and requires accelerated traffic mobility. Therefore, the author draws the conclusion that smart mobility innovation planning using artificial intelligence-based drones in Yogyakarta City can be an alternative solution for detecting road damage in Yogyakarta City through the implementation of generative adversarial network (GAN) method technology, CRDDC2022 dataset, data aggregator system, web application systems, and possible web-based decision support systems. The hope is that this innovation can improve the management of road infrastructure and the comfort of road users in using the city transportation system so that it can reduce the number of accidents and support sustainable optimization of smart cities.